Ethics-Driven Competitiveness: The Role of Sharia Compliance in Enhancing Financial and Strategic Capabilities of Indonesian SMEs - Suhirman, Gatot; Azizurrohman, Muhammad; Riqfi, Husni Muhammad; Abubakar, Herminawati (Universitas Brawijaya, Indonesia, 2025)
Indonesia’s retail SMEs face growing pressure to maintain competitiveness amidst economic uncertainty and increasing demands for financial transparency. This study examines how internal strategic capabilities, specifically market orientation and strategic financial practices, shape competitive advantage, with a focus on the mediating roles of innovation, resource allocation, and financial reporting quality. It also explores how Shariah Compliance Orientation moderates the relationship between financial practices and reporting quality. A quantitative, cross-sectional survey was conducted with 500 SME owners and managers across Java, Sumatra, Bali, and Sulawesi. Structural Equation Modeling using SmartPLS 4 was applied to assess the hypothesized relationships. The findings confirm that both market orientation and strategic financial practices significantly enhance competitive advantage. Strategic financial practices are also found to improve financial reporting quality, positioning it as a vital intangible asset. Innovation and resource allocation further mediate the effects of internal capabilities on firm performance. Moreover, Shariah Compliance Orientation strengthens the influence of financial discipline on reporting outcomes. By integrating Islamic ethical principles into the Resource-Based View and Dynamic Capabilities Theory, this study provides a culturally grounded and practically relevant framework for enhancing SME competitiveness in emerging markets.